PENINGKATAN KEMAMPUAN MAHASISWA DALAM PEMBELAJARAN MK LINGUISTICS AND EDUCATIONAL RESEARCH MELALUI METODE PROJECT-BASED LEARNING - Wulandari, Rini Susanti; Wahyuni, Sri; Syafri, Frimadhona (Lingua, 2016)
Every university in Indonesia requires that students who are in the final stage of the study to have the ability make up thesis about uncovering phenomena, facts, issues, analysis, and draw conclusions on the outcome of the analysis In addition to the competence of cognitive nature, thesis-making process also involves a wide range of practical competence necessary to write scientific papers, such as mastery of the intricacies of research methods and how to apply it in real activity. The course of Linguistics and Educational Research designed to provide insight into the understanding of research, types of research, research terminology, research designs, and other types of analysis required. The end product of this course is a research proposal. This study focuses on how to implement the Project Based Learning (PBL) in the class of Linguistic and Educational Research by following the steps of project development recommended by Sheppar & Stoller (1995). The main data that drawn from observations made in the form of quantitative data such as post-test value and portfolio. Setiap perguruan tinggi di Indonesia mewajibkan para mahasiswanya yang sudah berada pada tahap akhir studi untuk memiliki kemampuan menyusun skripsi untuk mengungkap fenomena, fakta-fakta, permasalahan, analisis, dan simpulan hasil analisis tersebut. Selain kompetensi yang bersifat kognitif, proses pembuatan skripsi juga melibatkan berbagai kompetensi praktis yang diperlukan untuk menulis karya ilmiah, misalnya penguasaan terhadap seluk-beluk metode penelitian dan cara mengaplikasikannya di dalam kegiatan nyata. Mata kuliah Linguistics and Educational Research didesain untuk memberikan wawasan tentang pengertian riset, jenis-jenis riset, terminologi riset, disain-disain riset, dan jenis-jenis analisis yang diperlukan. Produk akhir mata kuliah ini adalah sebuah proposal penelitian. Penelitian ini difokuskan pada pengimlementasian Procect Based Learning (PBL) pada kelas Linguistic and Educational Research dengan mengikuti langkah-langkah pengembangan proyek yang direkomendasikan oleh Sheppar & Stoller (1995). Data utama yang ditarik dari observasi yang dilakukan adalah berupa data-data kuantitatif berupa nilai post test dan portofolio.